Modelling the Health Policy Process: One Size Fits All or Horses for Courses? - Martin Powell; Russell Mannion (Kerman University of Medical Sciences, 2023)
A range of conceptual models for understanding the policy process have been applied to the health policy process, largely in particular sub areas or policy domains such as public health. However, these contributions appear to offer different rationales and present different frameworks for understanding the policy process. This Editorial critically examines articles that explore the health policy process with models from wider public policy and from health policy. It can be seen that very few of the wider models have been applied in studies of the health policy process. Conversely, some models feature in studies of the health policy process, but not in the wider policy process literature, which suggests that literature on the health policy process is semi-detached from the wider policy process literature. There seem to be two very different future research directions: focusing on 'home grown' models, or taking greater account of the wider policy process literature. Does 'one size fit all' or is it 'horses for courses'?